To what extent do somatotype structures affect athletic performance in professional athletes? - Terzi, E.; Kalkavan, A. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: This study aimed to ascertain the influence of somatotype structures on athletic performance among professional athletes. METHODS: Twenty-eight professional athletes, comprising 14 handball players and 14 volleyball players, were enlisted as participants for this study. As per the methodology, evaluations encompassing explosive power, strength, flexibility, horizontal jump, agility, sprint, and hand-foot reaction tests were conducted. Following physiological assessments, parameters including body mass index, body fat percentage, and somatotype were computed. The impact of athletes` somatotype structures on their athletic performance was investigated employing linear regression analysis. RESULTS: The endomorphy value serves as a negative predictor (r2=0.159) for explosive power, whereas the mesomorphy (r2=0.204) and ectomorphy (r2=0.379) values act as positive predictors of explosive power. Ectomorphy value negatively predicts grip strength (r2=0.399) and back strength (r2=0.214), while mesomorphy value positively predicts grip strength (r2=0.233) and back strength (r=0.338; r2=0.114). Mesomorphy value negatively predicts flexibility (r2=0.247), long jump (r2=0.311), sprint (r2=0.256), and reaction (r2=0.133), whereas ectomorphy value positively predicts flexibility (r2=0.225), long jump (r2=0.463), sprint (r2=0.393), and reaction (r2=0.208). CONCLUSIONS: This study showed a correlation between various somatotype structures and indicators of athletic performance. Within this framework, it can be inferred that mesomorphy and ectomorphy values serve as reliable predictors of athletes` performance. Furthermore, individuals with elevated mesomorphy values may exhibit enhanced strength performance, while those with higher ectomorphy values may demonstrate superior flexibility performance. Hence, when designing training programs aimed at enhancing athletes` performance attributes, it is imperative to account for the influence of body type on such performances.